Pengelolaan Rantai Pasok Tepung Di PT. Royal Coconut Kabupaten Minahasa Utara - Koloay, Adiel Remalya; Pakasi, Caroline Betsi Diana; Lolowang, Tommy Fredy (Sam Ratulangi University, 2024)
This research aims to describe and describe the management of the coconut flour supply chain at PT. Royal Coconut, North Minahasa Regency. This research was conducted for 2 months starting from June 2022 to July 2022. The data used in this research are primary and secondary data. Primary data was obtained through direct interviews with the company, suppliers and coconut farmers located at PT. Royal Coconut, while secondary, was obtained from relevant literature as well as documents and reports held by the company from related agencies. The sample used is snowball sampling, namely a technique for determining samples that are initially small in number, then increase in size. The respondents used were 5 traders and 1 coconut farmer. Based on the research results, it shows that the coconut flour supply chain actors PT. Royal Coconut is a supplier of raw materials including farmers, farmers who are also collectors, factories, namely PT. Royal Coconut, distributor to Surabaya head office, expedition services, retailers which are export destination countries and end up with consumers. The flow of information begins with the need for coconut flour from the Surabaya head office, coconut flour factories and then to farmers and growers who are also collectors. Financial flows take the form of consumer level payments to importirs, importirs to the Surabaya head office and then to the PT coconut flour factory. Royal Coconut is used for factory operations and purchasing coconut raw materials. The supply chain flow of coconut raw material material starts from raw material suppliers, namely farmers, collectors and growers who also act as collecting traders, then to the PT coconut flour factory. Royal Coconut Surabaya Head Office to destination countries and final consumers. Raw material procurement activities are carried out by suppliers who are divided into several areas in North Sulawesi, namely North Bolaang Mongondow, Minahasa, North Minahasa.